Cost-Effectiveness of “Golden Mustard” for Treating Vitamin A Deficiency in India - Chow, Jeffrey; Klein, Eili Y.; Laxminarayan, Ramanan (PLOS ONE, 2010)
Background Vitamin A deficiency (VAD) is an important nutritional problem in India, resulting in an increased risk of severe morbidity and mortality. Periodic, high-dose vitamin A supplementation is the WHO-recommended method to prevent VAD, since a single dose can compensate for reduced dietary intake or increased need over a period of several months. However, in India only 34 percent of targeted children currently receive the two doses per year, and new strategies are urgently needed. Methodology Recent advancements in biotechnology permit alternative strategies for increasing the vitamin A content of common foods. Mustard (Brassica juncea), which is consumed widely in the form of oil by VAD populations, can be genetically modified to express high levels of beta-carotene, a precursor to vitamin A. Using estimates for consumption, we compare predicted costs and benefits of genetically modified (GM) fortification of mustard seed with high-dose vitamin A supplementation and industrial fortification of mustard oil during processing to alleviate VAD by calculating the avertable health burden in terms of disability-adjusted life years (DALY). Principal Findings We found that all three interventions potentially avert significant numbers of DALYs and deaths. Expanding vitamin A supplementation to all areas was the least costly intervention, at 23–50 per DALY averted and 1,000–6,100 per death averted, though cost-effectiveness varied with prevailing health subcenter coverage. GM fortification could avert 5 million–6 million more DALYs and 8,000–46,000 more deaths, mainly because it would benefit the entire population and not just children. However, the costs associated with GM fortification were nearly five times those of supplementation. Industrial fortification was dominated by both GM fortification and supplementation. The cost-effectiveness ratio of each intervention decreased with the prevalence of VAD and was sensitive to the efficacy rate of averted mortality. Conclusions Although supplementation is the least costly intervention, our findings also indicate that GM fortification could reduce the VAD disease burden to a substantially greater degree because of its wider reach. Given the difficulties in expanding supplementation to areas without health subcenters, GM fortification of mustard seed is an attractive alternative, and further exploration of this technology is warranted.